Modeling the Psychological Determinants of Digital Addiction: The Mediating Roles of Loneliness, Self-Control, and Emotional Dysregulation - Laprade , Danielle; Nazarpour , Babak; Stanley, Frederick (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: This study aimed to model the psychological determinants of digital addiction among Canadian adults by examining the direct and indirect effects of loneliness, self-control, and emotional dysregulation within an integrated structural equation model. Methods and Materials: This quantitative cross-sectional correlational study was conducted among 642 adults residing in Canada who reported regular daily use of digital technologies. Participants completed standardized self-report measures assessing digital addiction, loneliness, self-control, and emotional dysregulation. Data were analyzed using IBM SPSS Statistics version 29 and AMOS version 29. Preliminary analyses included assessment of normality, reliability, convergent validity, and correlations among study variables. The hypothesized relationships among the constructs were tested using structural equation modeling with maximum likelihood estimation. Model fit was evaluated using χ²/df, CFI, TLI, GFI, AGFI, RMSEA, and SRMR. Indirect effects were examined through bootstrap resampling with 5,000 samples and bias-corrected 95% confidence intervals. Findings: The measurement model demonstrated satisfactory fit to the data, χ²/df = 2.11, CFI = .970, TLI = .966, GFI = .941, AGFI = .929, RMSEA = .042, and SRMR = .039. Digital addiction was positively associated with loneliness and emotional dysregulation and negatively associated with self-control. In the structural model, emotional dysregulation significantly predicted digital addiction (β = .42, p < .001), self-control significantly and negatively predicted digital addiction (β = −.39, p < .001), and loneliness significantly predicted digital addiction (β = .23, p < .001). Loneliness significantly predicted emotional dysregulation (β = .48, p < .001) and negatively predicted self-control (β = −.37, p < .001), while emotional dysregulation negatively predicted self-control (β = −.46, p < .001). Bootstrap results confirmed significant indirect effects of loneliness on digital addiction through emotional dysregulation and self-control. The final model explained 68% of the variance in digital addiction. Conclusion: The findings indicate that digital addiction is shaped by interconnected interpersonal, emotional, and self-regulatory mechanisms. Loneliness contributes to problematic digital use both directly and indirectly by increasing emotional dysregulation and weakening self-control. These results highlight the importance of addressing emotional regulation, self-control, and social connectedness in prevention and intervention programs for digital addiction.